KAJIAN KINERJA KEFARMASIAN DI RUMAH SAKIT Dr. FERDINAND LUMBANTOBING SIBOLGA TAHUN 2020 - Pandiangan, Donna (Jurnal Inovasi Kesehatan Masyarakat, 2021)
The General Hospital of Dr. Ferdinand Lumbantobing Sibolga as a class B hospital has been accredited Plenary based on Hospital Accreditation Committee Letter Number: KARS-SERT / 569 / I / 2017 dated January 5, 2017. Changes in the paradigm of pharmaceutical services from previously oriented to medicine to patient-oriented demand pharmacists can provide quality pharmaceutical services, interact directly with patients, and are responsible for the drugs given by referring to Permenkes 72, 2016 regarding pharmaceutical service standards even though in practice they have not met the established standards. Performance can be interpreted as the output of the work done and also the process towards the expected results of a job. Many factors underlying pharmaceutical performance include individual variables (ability, education), organizational variables (service procedures), psychological variables (motivation). The problem of implementing a patient safety system is the occurrence of patient safety incidents (IKP) due to lack of optimal pharmaceutical services related to the limitations of human resources (HR) and the consistent implementation of operational standards.